Semiotic Analysis Mineral Water Advertisement 2017 And 2022: Revealing Symbolic Meanings And Cultural Signifiers - Annisa Luluk Firdausie; Santi Agustin (Jurnal Pendidikan dan Sastra Inggris, 2024)
This article discusses the semiotic study of mineral drink advertisements version "2017 and 2022. The research is focused on the signs contained in "Mineral Drink Advertisements versions 2017 and 2022" so that the meaning and message are well conveyed to consumers or the public. The ad provides an educative and creative story message. A qualitative descriptive research method with semiotic analysis techniques with Roland Barthes' theory which contains connotative and dotative meanings. The results of the study show that the "2017 and 2022 version of the mineral drink advertisement" contains continuous nonverbal and verbal sign messages so that it has its on meaning. The ad contains one of the local mineral water products in Indonesia which is also correlated with an ad that is very close to the culture and habits of the Indonesian people. As explained how the advertisement represents two Indonesian cultures when celebrating the month of Ramadan or when fasting, and Indonesian culture when welcoming guests. The advertisement does not only represent deeper Indonesian culture, but also serves as literature for the development of marketing ideas for company owners by incorporating cultural elements and the needs of market forces